2016
DOI: 10.1021/acsnano.6b05409
|View full text |Cite
|
Sign up to set email alerts
|

Stealth Immune Properties of Graphene Oxide Enabled by Surface-Bound Complement Factor H

Abstract: With mounting evidence that nanomaterials can trigger adverse innate immune responses such as complement activation, there is increasing attention to the development of strategies that mask the complement-activating properties of nanomaterials. The current gold standard to reduce complement activation of nanomaterials is the covalent attachment of polymer coatings on nanomaterial surfaces, even though this strategy provides only moderate protection against complement activation. Akin to protein coronas that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 96 publications
1
41
0
1
Order By: Relevance
“…Li et al similarly observed increased biocompatibility for GO coated with BSA and polyethylene glycol (PEG) . Furthermore, Belling et al demonstrated that albumin adsorption onto the GO surface, partially prevented complement activation . It is reasonable to believe that similar effects are observed with our formulation, which helps to explain the lower cytotoxic effects observed in relation to previously reported data.…”
Section: Discussionsupporting
confidence: 84%
“…Li et al similarly observed increased biocompatibility for GO coated with BSA and polyethylene glycol (PEG) . Furthermore, Belling et al demonstrated that albumin adsorption onto the GO surface, partially prevented complement activation . It is reasonable to believe that similar effects are observed with our formulation, which helps to explain the lower cytotoxic effects observed in relation to previously reported data.…”
Section: Discussionsupporting
confidence: 84%
“…Complement proteins opsonize pathogens and cells for engulfment via complement receptors and could conceivably promote nanomaterial uptake as well. However, certain complement factors may instead confer “stealth” properties to nanomaterials by preventing further complement activation, as shown in a recent study on GO (43). Complement activation also liberates two potent effector molecules (C3a and C5a) that play important roles in the recruitment and activation of inflammatory cells as well as anaphylaxis, a serious allergic reaction that is rapid in onset and may cause death (44).…”
Section: Bio-corona Formation: Shelter From the Stormmentioning
confidence: 99%
“…In another approach, Thaxton et al synthesized a suite of high-density lipoprotein-liked NPs which functions to scavenge and neutralize LPS, inhibiting TLR-4 dependent inflammatory response [70]. Moreover, Cho et al demonstrated that NPs coated with negative regulatory complement factor H can prevent complement activation with >90% efficiency [71]. And galactose polymer modified NPs could absorbed complement H protein on their surface in vitro , providing a low level of complement activation [72].…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%